First taste of freedom : a cultural history of bicycle marketing in the United States - Turpin, Robert J. (Sports and entertainment., 2018)
"First Taste of Freedom" is a work of American cultural history focused on the bicycle market in the United States. A primary goal of the research was also to understand how the bicycle can be seen so differently in the US as opposed to other countries"--